NUMBER OF OVULATIONS PER ESTROUS CYCLE IN ANDINA AND PERU GUINEA PIG (Cavia porcellus) BREEDS - Araníbar, Eduardo (2014)
The aim of the study was to determine the average number of ovulating follicles inthe Andina and Peru guinea pigs breeds in order to know if the difference in litter sizebetween the two breeds is partly due to the number of ovulations. Fifteen animals of 10weeks of age per breed were used. The day of ovulation was considered as day 0 of theestrous cycle and was determined through vaginal cytology and absence of the vaginalmembrane. In day 8 of the estrous cycle vaginal cytology was done to verify that the female was in diestrus and then animals were slaughtered to obtain the ovaries. Thesewere fixed with buffered formalin and histological sections of ovaries were stained withhematoxylin eosin. The samples were observed in optical microscope and corpus lutea(CL) were counted. The Andina breed had 3.6 ± 0.9 CL and the Peru breed had 2.8 ± 0.9 CL(p<0.05). The difference in litter size between the two breeds would be partially due to thehigher number of ovulations per estrous cycle in the Andina breed as compared to thePeru breed.